Improved Profitability by Optimising Working Capital : Evidence from Nasdaq OMXH 2002−2018 - Hänninen, Heikki (My University, 2022)
Efficient working capital management is one of the most important ways of improving operational performance. Financial working capital management may provide companies with a competitive advantage and improve profitability. It is essential to conduct research about how companies operate and handle their short-term finances. It is a representation of management's responsiveness to changing circumstances as well as operational and financial success. Furthermore, studies on working capital consider whether a positive or negative NWC is optimal. In this thesis the impact of working capital on company profitability in Finnish listed companies is studied. The lack of research on the short-term performance of Finnish listed companies through two financial crises over 2002−2018 is analysed with multiple different regressions. The working capital is measured by the cash conversion cycle, which is comprised of accounts payables, accounts receivables and inventories. Along with other commonly used independent variables the profitability of the listed companies is estimated using OLS, fixed effects, and random effects models. The results of this thesis show that there are statistically significant relationships between the cash conversion cycle components and profitability. The outcomes of the estimations were contrasted with the majority of working capital literature and research. The sample's findings demonstrated that working capital had no real influence on the profitability indicators in listed companies during these difficult economic times. Although the results were statistically significant, their economic significance for all companies may essentially be ignored.

Tehokas käyttöpääoman hallinta on yksi tärkeimmistä keinoista parantaa operatiivista suorituskykyä. Taloudellinen käyttöpääoman hallinta voi tarjota yrityksille kilpailuetua ja parantaa kannattavuutta. On olennaisen tärkeää tehdä tutkimusta siitä, miten yritykset toimivat ja käsittelevät lyhytaikaista rahoitustaan. Käyttöpääoma kuvaa johdon reagointikykyä muuttuviin olosuhteisiin sekä operatiivista ja taloudellista menestystä. Lisäksi käyttöpääomaa koskevissa tutkimuksissa pohditaan, onko positiivinen vai negatiivinen käyttöpääoma optimaalinen yrityksen kannalta. Tässä tutkielmassa tutkitaan käyttöpääoman vaikutusta yrityksen kannattavuuteen suomalaisissa pörssiyhtiöissä. Tutkimuksen puutetta suomalaisten pörssiyhtiöiden lyhyen aikavälin suorituskyvystä kahden finanssikriisin aikana vuosina 2002–2018 analysoidaan useilla eri regressioanalyyseillä. Käyttöpääomaa mitataan käyttöpääomasyklillä, joka muodostuu ostoveloista, myyntisaamisista ja varastoista. Yhdessä muiden yleisesti käytettyjen riippumattomien muuttujien kanssa pörssiyhtiöiden kannattavuutta estimoidaan OLS-, kiinteiden vaikutusten ja satunnaisvaikutusten malleilla. Tämän tutkielman tulokset osoittavat, että käyttöpääomasyklin osatekijöiden ja kannattavuuden välillä on tilastollisesti merkitsevä yhteys. Estimointien tulokset asetettiin vastakkain suurimman osan käyttöpääomaa koskevasta kirjallisuudesta ja tutkimuksesta kanssa. Otoksen tulokset osoittivat, että käyttöpääomalla ei ollut todellista vaikutusta pörssiyhtiöiden kannattavuusindikaattoreihin näinä vaikeina taloudellisina aikoina. Vaikka tulokset olivat tilastollisesti merkitseviä, niiden taloudellinen merkitys kaikkien yritysten kannalta voidaan periaatteessa jättää huomiotta.
Keywords: working capital, profitability, working capital management, cash conversion cycle